2017
DOI: 10.1007/s12247-017-9273-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Analytical and Sampling Errors in the Prediction of the Active Pharmaceutical Ingredient Concentration in Blends From a Continuous Manufacturing Process

Abstract: Purpose A near-infrared (NIR) spectroscopic method was developed for real time analysis of the active pharmaceutical ingredient (API) in blends from a continuous manufacturing process. The sampling and analytical errors of these determinations were estimated through variographic analysis. Methods Thirty-three calibration blends were prepared in laboratory scale equipment with a concentration range spanning from 70 to 130% of API target concentration. The NIR calibration model was validated using three independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…PAT monitoring is governed by the same principles as those defined by the theory of sampling. ,, Although the literature shedding light on the impact of the position of PAT probes used to monitor liquids is limited, it is well-recognized that the lack of mixing and poor choice of probe angle and depth might lead to spatial heterogeneity of suspended particles in stirred crystallizers/tanks. ,, Particularly, it has been demonstrated that the signal quality for probe designs with flow-through gaps/slids/cells, as employed in the CCSA (Figure S3 in the Supporting Information), , strongly depends on the hydrodynamic conditions influenced by the probe orientation, angle, and immersion depth. , Arbitrary placement of PAT probes can lead to stagnant liquid accumulating in the probe gaps/slids/cells resulting in nonrepresentative and fluctuating measurements of the bulk properties . In the present work, it was attempted to align the cell of the CCSA probe along the liquid motion in the crystallizer (Figure S3 in the Supporting Information) to permit unrestricted flow through the measuring cell without claiming to have achieved optimized conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAT monitoring is governed by the same principles as those defined by the theory of sampling. ,, Although the literature shedding light on the impact of the position of PAT probes used to monitor liquids is limited, it is well-recognized that the lack of mixing and poor choice of probe angle and depth might lead to spatial heterogeneity of suspended particles in stirred crystallizers/tanks. ,, Particularly, it has been demonstrated that the signal quality for probe designs with flow-through gaps/slids/cells, as employed in the CCSA (Figure S3 in the Supporting Information), , strongly depends on the hydrodynamic conditions influenced by the probe orientation, angle, and immersion depth. , Arbitrary placement of PAT probes can lead to stagnant liquid accumulating in the probe gaps/slids/cells resulting in nonrepresentative and fluctuating measurements of the bulk properties . In the present work, it was attempted to align the cell of the CCSA probe along the liquid motion in the crystallizer (Figure S3 in the Supporting Information) to permit unrestricted flow through the measuring cell without claiming to have achieved optimized conditions.…”
Section: Resultsmentioning
confidence: 99%
“…PAT monitoring is governed by the same principles as those defined by the theory of sampling. 2,69,72 Although the literature shedding light on the impact of the position of PAT probes used to monitor liquids is limited, 73 it is well-recognized that the lack of mixing and poor choice of probe angle and depth might lead to spatial heterogeneity of suspended particles in stirred crystallizers/ tanks. 23,37,74−76 Particularly, it has been demonstrated that the signal quality for probe designs with flow-through gaps/slids/ cells, as employed in the CCSA (Figure S3 in the Supporting Information), 37,38 strongly depends on the hydrodynamic conditions influenced by the probe orientation, angle, and immersion depth.…”
Section: Solvent-mediated Polymorphic Phase Transformation Of Ffa Iii...mentioning
confidence: 99%
“…Adapting an in-line PAT method, such as a NIR spectroscopic method, for analyzing content uniformity of powder in the feed frame provides opportunities to assure the quality of tablets in the late stages of tablet manufacturing. Near-infrared spectroscopy has been used in-line for blend uniformity determination at locations before compression, such as at the exit of blenders, 6 mixers 7 and twin screw granulators, 8 or inside feed chutes 9,10 and feed frames. 1115 The feed frames have been identified as a reliable location to achieve representative sampling of blends.…”
Section: Introductionmentioning
confidence: 99%